Joymath Cognitive Behavioral Intervention to Enhance Numeracy Literacy and Mathematical Resilience at At-Tanzil Learning Center: Intervensi Joymath Cognitive Behavioral dalam Peningkatan Literasi Numerasi dan Resiliensi Matematis di Sanggar Belajar At-Tanzil - Nafida Hetty Marhaeni; Nanang Khuzaini; Lukman Jakfar Shodiq; Kholis Frendika (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Children of Indonesian migrant workers in Malaysia face dual challenges of limited access to formal education and low numeracy literacy, often compounded by severe math anxiety. This community service program aimed to enhance numeracy literacy and mathematical resilience through an integrative Joymath–Cognitive Behavioral Therapy (CBT) intervention in a non-formal education setting. The implementation adopted a Participatory Action Research (PAR) approach involving 25 students at Sanggar Belajar At-Tanzil, Selangor. The intervention was conducted in three stages: psychological conditioning to reduce baseline anxiety, concept exploration through joyful mathematics games, and cognitive restructuring to address negative self-talk. Program outcomes were assessed using participatory observation, indicators of student engagement, and analysis of students’ worksheets (LKPD). The findings showed promising effectiveness, marked by increased active participation, a shift in students’ self-narratives from helplessness to curiosity, and improved understanding of basic mathematical concepts. Beyond student outcomes, the program strengthened the partner learning center’s capacity by introducing a practical, context-sensitive instructional model that can be sustained in non-formal settings serving vulnerable learners.